2016
DOI: 10.5424/fs/2016251-07036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, pH and carbon and nitrogen sources on growth of in vitro cultures of ectomycorrhizal isolates from Pinus heldreichii forest

Abstract: Aim of study: This study aims to provide basic information about physiological characteristics of isolates of Lactarius deliciosus (L.) Gray, Russula sanguinaria (Schumach.) Rauschert, Suillus collinitus (Fr) Kuntze, Suillus granulatus (L.) Rousell, Tricholoma batchii Gulden and Tricholoma imbricatum (Fr.) Kumm.Area of study: The isolates are obtained from Pinus heldreichii H. Christ forest in the south-eastern part of Montenegro. Material and methods:The isolates were molecularly characterised by internal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…The results showed that, in general, R. luteolus tends to grow better under acidic than alkaline conditions. This finding agrees with the trends mentioned by Hung and Trappe (1983), Lazarević et al (2016) and Willenborg et al (1990), who mentioned that ECMF have in general, an acidophilic nature when grown under pure culture conditions. However, it is important to mention that there are some exceptions either specific or intraspecific, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results showed that, in general, R. luteolus tends to grow better under acidic than alkaline conditions. This finding agrees with the trends mentioned by Hung and Trappe (1983), Lazarević et al (2016) and Willenborg et al (1990), who mentioned that ECMF have in general, an acidophilic nature when grown under pure culture conditions. However, it is important to mention that there are some exceptions either specific or intraspecific, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have shown that the ectomycorrhizal mycelium might be very sensitive to temperature variations (Lazarević et al, 2016;Marx et al, 1970;Sánchez et al, 2001). If the soil dramatically cools, the metabolic activity of the fungi and the roots decrease, with negative consequences for mycelial growth and nutrient availability for both the fungi and the associated plants (Lazarević et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations